Mycobacterium tuberculosis strains of the Beijing genotype are rarely observed in tuberculosis patients in South America - Suffys, Philip N. (2008)
AUTHORS - Viviana Ritacco/+, Beatriz López, Patricia I Cafrune1, Lucilaine Ferrazoli2, Philip N Suffys3, Norma Candia4, Lucy Vásquez5, Teresa Realpe6, Jorge Fernández7, Karla V Lima8, Jeannete Zurita9, Jaime Robledo6, Maria L Rossetti1, Afranio L Kritski10, Maria A Telles2, Juan C Palomino11, Herre Heersma12, Dick van Soolingen12, Kristin Kremer12, Lucía Barrera. AFFILIATIONS - Instituto Nacional de Enfermedades Infecciosas ANLIS Carlos Malbrán, Vélez Sarsfield 563, 1281 Buenos Aires, Argentina 1Universidade Federal do Rio Grande do Sul, Porto Alegre, RS, Brasil 2Instituto Adolfo Lutz, São Paulo, SP, Brasil 3Instituto Oswaldo Cruz-Fiocruz, Rio de Janeiro, RJ, Brasil 4Instituto de Investigaciones en Ciencias de la Salud, Asunción, Paraguay 5Instituto Nacional de Salud, Lima, Peru, 6Corporación para Investigaciones Biológicas, Medellín, Colombia 7Instituto de Salud Pública de Chile, Santiago, Chile 8Instituto Evandro Chagas, Belém, Brasil 9Hospital Vozandes, Quito, Ecuador 10Universidade Federal do Rio de Janeiro, Rio de Janeiro, RJ, Brasil 11Institute of Tropical Medicine, Antwerp, Belgium 12National Institute of Public Health and the Environment, Bilthoven, The Netherlands.